A Comparative Evaluation of the Performance of SDN Controllers (ONOS) using DOCKER Container - Abdullah Mohammed , Ghazwan; Ibrahim Aldabbagh, Omar Abdulmonem (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
software-defined networks SDN represents a significant shift in the networking field through the ability to solve problems facing traditional networks, such as updating components for networks and integration between devices. Open-source components and protocols were used in SDN. Among its advantages are the separation of the control plane from the data plane, the use of the OpenFlow protocol, and the transition to Decentralization in network management. In SDN, there are several types of controllers. In this paper, work has been done on ONOS controllers in cluster mode from one to five controllers, and a comparison between the performance of different numbers of controllers to obtain the best performance through the use of Cbench. It was found that using one or two controllers achieves the best performance